Sosialisasi Tingkat Kesadaran dan Pengetahuan Masyarakat Tentang Manfaat Teh Kombucha Dalam Mengatasi Sleep Paralysis Selama Pandemi COVID-19 - Saristiana, Yuneka; Prasetyawan, Fendy; Arifin, Chandra; Rofiq, Abd; Astutik, Widhi; Azis, Asrizal; Tri Wulan, Ema (Journal of Social and Community Service, 2022)
This community service program aims to enhance public understanding and knowledge about sleep paralysis and the benefits of kombucha tea during the COVID-19 pandemic. Conducted throughout January 2021, the program involved various socialization activities such as presentations, workshops, and discussions. Post-activity evaluations showed a significant improvement in public understanding of sleep paralysis and the benefits of kombucha tea. Prior to the program, most respondents had limited knowledge about sleep paralysis and kombucha tea, but after participating, their understanding increased significantly. Despite facing some challenges, the overall results of this program indicate that socialization about sleep paralysis and the benefits of kombucha tea can be effective in enhancing public understanding of sleep health and nutrition during the COVID-19 pandemic.